In vitro fertility test of human spermatozoa membrane protein fertilin beta antibody in mice (mus musculus balb/c) as immunocontraceptive candidate - I'tishom, Reny; Soebadi, Doddy M; Hinting, Aucky; Lunardhi, Hamdani; Yudiwati, Rina (Folia Medica Indonesiana, 2017)
One of the materials as potential candidates immunocontraception material is spermatozoa. Fertilin beta is spermatozoa membrane protein and is found only in mature spermatozoa and ejaculate, which serves as an adhesion molecule. Spermatozoa membrane protein that is used as an ingredient immunocontraception candidate, must have specific criteria that the specificity of spermatozoa, the role of antigen in the fertilization process, which includes the formation of immunogenicity sufficient antibody response has the potential to block fertilization. Antibodies against spermatozoa affect the stages before fertilization of the reproductive process and can hinder the development of the embryo after fertilization. Until now very little research data spermatozoa membrane protein as an ingredient immunocontraception are up to the test of experimental animals. The research objective is to prove the role of the resulting antibody induction of antibodies fertilin beta protein in the membrane of human spermatozoa induce agglutination and reduce motility thus reducing the number of in vitro fertilization. Research conducted at the IVF Laboratory, Department of Biology of Medicine, Faculty of Medicine, University of Airlangga. This research includes: Test the potential of antibody protein beta fertilin membrane of human spermatozoa and inhibit the role of antibodies in vitro fertilization in mice (Mus musculus Balb/c). In vitro studies have resulted in fertilization figure of 25% is smaller than the number that is equal to control fertilization of 58.7%, whereas previously the spermatozoa were incubated first with a beta membrane protein antibody fertilin human spermatozoa. While the percentage of inhibition of sperm to fertilize an oocyte by 33.75%. Potential imunokontraseptif considered effective if it decreased significantly (P <0.05) than the numbers fertilization in the treatment group compared with the control group. This shows fertilin beta membrane protein antibody has the ability to inhibit human spermatozoa to fertilize oocytes that reduce the number of fertilization.